Model Inovatif Pembelajaran Kolaboratif dan Pengaruhnya terhadap Kemampuan Berpikir Kritis Siswa - Yuwana, Yuwana (Jurnal Pendidikan Dirgantara, 2025)
This study examines how working together in a group affects the critical thinking skills of junior high school students. The reason for this study is because students' critical thinking skills are not very strong, especially because their learning is too dependent on teachers. Collaborative learning is thought to help students be more engaged, talk to each other, and better understand and assess information. This study used a descriptive qualitative method, collecting data through questionnaires given to 27 ninth-grade students. The tools used check things like how active students are in the discussion, how well they can explain their ideas clearly, as well as how often they think about and check the ideas and information they hear. The results showed that most students liked the group learning method and believed that their critical thinking skills had improved after participating in the activity. In addition, students feel more confident in expressing opinions, are more able to listen to the views of their peers, and are more likely to understand the material being discussed. These findings confirm that working together in a group is an effective learning strategy to enhance critical thinking while encouraging students' active participation in the classroom.